Peranan Faktor Usia Dalam Memoderasi Pengaruh Pemberian Insentif Terhadap Motivasi Kerja Karyawan Kantor Direksi PT. PG. Rajawali I Surabaya - Hafiz Hermawan; Siti Sulasmi (Universitas Airlangga, 2014)
One of the company's efforts made in motivating employees is by giving rewards, such rewards are in the form of incentives. In order that these incentives can motivate employees, incentives given to companies can be either Monetary Incentive or Non-Monetary Incentives depending on how the appeal or the importance of the incentives for employees. But there are a few things to note companies, particularly with regard to the granting of incentives to boost employee motivation. Because in providing various forms of incentives to employees, the company needs to know the demographic characteristics of the employees as factors that can strengthen or weaken the relationship between incentives and employee motivation. One of the demographic characteristics of the form factor is the age of an employee, an employee who has a younger age it might be more motivated if the company gives incentives rather than a more senior employee. This is because a person's motivation in working for tend to be changed along with the increase of age. Employees with a younger age will likely pursue the monetary in the work, while employees who have senior will be more likely pursue the achievement of the monetary. Population and sample which became the object of this research is the 36 employees of PT. PG. Rajawali I. The results of the study prove that Monetary Incentives and Non Monetary Incentives give significant effects either simultaneously or partial employee motivation of PT. PG. Rajawali I. Whereas the moderation effect of age factor is not significantly strengthen the impact of influence the granting of providing Monetary Incentives and Non Monetary Incentives of employee motivation PT. PG. Rajawali I.